MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE SQ3R PADA PEMBELAJARAN SEJARAH KELAS XII SMA NEGERI 1 TEMBILAHAN HULU - Wardiah (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Low activity, student creativity in the learning process can result in the teaching and learning process being less than optimal so that the material presented is incomplete according to the expected completeness criteria. From the results of observations and discussions with the history subject teacher, information is obtained that the learning system has not fully involved students as the subject of learning consequently the final result to be achieved, namely individual and classical learning completeness with KKM (minimum completeness criteria) has not been achieved. One of the efforts made to improve the process and student learning outcomes, a learning method is used that makes it easier for students to compile and understand information or the content of the lesson text in increasing understanding of social studies subject matter so that learning outcomes are expected to increase, through the use of the SQ3R method. Based on the background of the problem, the formulation of the problem in this study is: